STRATEGI PENGEMBANGAN KAWASAN WISATA PANTAI PANJANG BENGKULU, DITINJAU DARI PERSPEKTIF WISATAWAN DAN MASYARAKAT LOKAL - Fikri Pratama, Handika; Sakti, Budiman (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2016)
The purpose of this study was to identify potential tourist attraction, reviewing internal environmental conditions (such as their strengths and weaknesses) and external environmental conditions (such as opportunities and threats), and review the appropriate tourism development program in the Long Beach-based to tourists and local community perspective. The analytical method used in this study, namely diskritif analysis to identify the availability of infrastructure and the potential and power trarik travel and quantitative analysis with the help of Matrix IFAS and EFAS matrix. The number of respondents who were taken by accidental sampling of 100 respondents. The results showed that the potential tourist attraction located in Long Beach with a score of +0.910 internal factors and external factors with a score of +1.90. Thus the position in the grand strategy matrix (matrix internal-external) are in a position with a growth strategy occupies one cell in the matrix. A cell's position one shows the strategy to grow and establish (Rapid growth strategy), strategies to increase the growth rate of tourist arrivals with a faster time (the second year is greater than the first year and thereafter), improving the quality of that factor into force in order to maximize the utilization of all the opportunities (grand strategy). Tapak Padri development efforts and Beach Jakat sustainable (sustainable). Key Words: Grand Strategy, Tourism Development Program